IMPLEMENTASI PROGRAM INDONESIA SEHAT PENDEKATAN KELUARGA PADA PRIORITAS CEKAL HIPERTENSI - Mujito, Mujito; Martiningsih, Wiwin; Mugianti, Sri; Anam, Agus Khoirul; Abiddin, Andi Hayyun (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Prevention of hypertension through controlling risk factors in hypertensive clients in the family can reduce the occurrence of complications so that a better quality of life is achieved. The method applied uses empowering family potential as a health promotion intervention strategy in controlling hypertension with community involvement and training of cadres with the method of question and answer lectures and demonstrations. The results show an increase in knowledge, namely the good category remains 5Percent and the very good category increases 95Percent. Improvement of skills, namely 86Percent are able to measure blood pressure with a digital tension meter, 86Percent are able to measure TB, BB and BMI calculations, 19Percent are able to measure cholesterol, blood sugar, uric acid, and 100Percent are able to record cards to healthy non communicable disease risk factors (KMS FR PTM). A hypertension care family group was formed with the Active Alert Village development approach, namely from, by and for the community. Increased participation of families and clients at risk of hypertension. Establishment of partnerships and assistance to family groups caring for hypertension. Families at risk of hypertension are expected to participate more actively in obtaining hypertension risk factor detection services.